Investigating factors in the implementation of customer relationship management in Polish enterprises - Agnieszka Bojanowska; Katarzyna Łukasik-Stachowiak; Katarzyna Toborek (International Entrepreneurship Review)
Objective: The article aimed to determine the factors of the implementation and functioning of customer relationship management (CRM) in Polish enterprises, whether they see the benefits and whether they can identify the reasons for choosing specific software and its supplier in the field of CRM systems, and whether the collected data is subjected to effective analyses. The research problem is to determine the determinants of the implementation and operation of the CRM system in Polish enterprises. Due to the lack of detailed research on this topic among Polish enterprises and the emerging need for more and more frequent use of the CRM system, the article attempts to examine this issue.